(untitled) (Journal of Universal Excellence, 2026)
Research Question (RQ): The article analyzes the impact of organizational climate on business performance of the Slovenian Tourist Agencies (TA). Purpose: Examine the impact of organizational climate on business performance of TA and through a questionnaire carried out a quantitative survey in Slovenian TA. Method: The collected survey data were analyzed by the following statistical methods: descriptive analysis, factor analysis and principal component analysis, multiple regression analysis and structural equation methods. Organization: Managers have to give a greater influence to the organizational climate (internal relations, leadership by delegating work, loyalty to the organization, career development, employee satisfaction and reward and professional training and learning) as a factor in business success. Society: To inform the owners, managers and heads of TA, as well as others that the organizational climate is important for all stakeholders and it is necessary to promote its increasing importance. Originality: It is the first such study in Slovenia and one of the first in the world literature. Limitations / further research: The questionnaire was aimed at owners / managers / managers and other employees in the TA and their branches, but not to their business partners, which contribute greatly to quality of services in TA. Suggestions for further research are in longitudinal research, and also in the fact that in the research are also included any other country and then compare the data.